EFL PRE-SERVICE TEACHERS' PROFESSIONAL IDENTITY CONSTRUCTION DURING TEACHING PRACTICUM - Firima Zona Tanjung, - (2022)
Professional identity construction significantly contributes to pre-service teachers' readiness for their teaching career in the future. Despite the abundance of research studies investigating the professional identity construction of pre-service teachers during the teaching practicum, the research on EFL pre-service teachers constructing their professional identity in the Indonesian context, mainly in the border area, seems to have remained untouched. The current study aimed to scrutinize the factors, critical events, and EFL pre-service teachers' process of envisioning themselves in the future regarding their participation in the teaching practicum program. Employing an intrinsic case study, four seventh-semester students of the English Education study program at a public university in North Kalimantan were involved as the participants. The data were collected through observation, reflective journals, interviews, and related documents. All data were then analyzed using a coding system and coding cycle. The findings revealed that the factors contributing to the professional identity were past learning experiences, institutional policies, mentorship, and the school community relationship. The critical events the participants mentioned included students' misbehavior, complicated political-social issues, and complex cultural negotiations. With different teaching experiences and teaching contexts, each participant differed in imagining their future selves and consequently in constructing their professional identity. The findings carry strategic and broad implications for building a solid tripartite partnership between student teachers, university, and school. Furthermore, pedagogical implications also call for the courses addressing EFL pre-service teachers' needs of various socially and culturally situated teaching contexts, skills, and preparation before being involved in the teaching practicum in order to help these prospective teachers construct their professional identity gradually.